2011
DOI: 10.1155/2011/895857
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Activities and the Mechanisms of Anti‐Inflammation of Asiatic Acid in Mice

Abstract: Asiatic acid (AA), a pentacyclic triterpene compound in the medicinal plant Centella asiatica, was evaluated for antinociceptive and anti-inflammatory effects. Treatment of male ICR mice with AA significantly inhibited the numbers of acetic acid-induced writhing responses and the formalin-induced pain in the late phase. In the anti-inflammatory test, AA decreased the paw edema at the 4th and 5th h after λ-carrageenan (Carr) administration and increased the activities of catalase (CAT), superoxide dismutase (SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 42 publications
3
89
0
Order By: Relevance
“…6,7) Asiatic acid isolated from P. chinensis has several health benefits and has thus attracted medical and research professionals. Previous studies have shown that Asiatic acid has a variety of pharmacological effects on anti-inflammation, 8,9) anti-tumor, 10) neuroprotection. 11) In particular, Asiatic acid has been shown to be a hepatoprotective agent.…”
mentioning
confidence: 99%
“…6,7) Asiatic acid isolated from P. chinensis has several health benefits and has thus attracted medical and research professionals. Previous studies have shown that Asiatic acid has a variety of pharmacological effects on anti-inflammation, 8,9) anti-tumor, 10) neuroprotection. 11) In particular, Asiatic acid has been shown to be a hepatoprotective agent.…”
mentioning
confidence: 99%
“…Polyphenols act as antioxidants via several mechanisms including the scavenging of free radicals and chelation of transition metals, as well as the mediation and inhibition of enzymes [19]. The use of traditional medicine is widespread and plants still present a large source of natural antioxidants that might serve as leads for the development of novel drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the aqueous and alcoholic extract of C. asiatica showed 46.31% and 71.18%, respectively, inhibition of edema after 3 hrs, while the standard ibuprofen showed an inhibition of 66.66% [38]. At the 4 th and 5 th hrs, after λ-carrageenan (Carr) supplementation, the asiatic acid reduced paw edema by regulation of catalase, superoxide dismutase (SOD), and glutathione in the liver tissue [39]. In another study, measurement of paw size was taken before carrageenan injection and then 1, 2, 3, and 4 hrs after carrageenan injection.…”
Section: Anti-inflammatory Activitymentioning
confidence: 98%